Business trends and impact of authorized dealership to Zagu Foods Corp - Ranada, Marc Constantine G.; Cosare, Brylle Aldrin E. (Manila: National University, 2010)
The study will discuss the business trends in the recent years with focus on Zagu's business
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- Chapter 1. The Problem and its Setting -- Chapter 2. Related Literature and Study -- Chapter 3. Research Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary of Findings, Conclusions, and Recommendations -- Bibliography -- Appendices.
Includes bibliographical references.